A simple and expedient protocol for the formation of furan-fused pyrimidine-containing phenol via a constructive multicomponent reaction under ambient conditions - Mahmoud Nassiri; Jaber Salehzadeh; Zahra Dehghani; Parisa Babaei (Results in Chemistry)
A novel, and efficient for the synthesis of furan-fused pyrimidine-containing phenol derivatives 4a–j via a one-pot multicomponent reaction is reported. The reaction employs aryl glyoxals, 1,3-dicarbonyl compounds, and 2-tert-butyl-4-methylphenol (TBMP) under ambient conditions in acetone and in the presence of triethylamine is reported. Optimization studies revealed acetone as the optimal solvent, delivering products in excellent yields (89–94 %) within 2.5 h at room temperature. Structural elucidation of the synthesized compounds was achieved through spectroscopic techniques (1H NMR, 13C NMR, and IR), mass spectrometry, and elemental analysis. This method offers significant advantages, including operational simplicity, mild reaction conditions, high atom economy, and environmental friendliness. Given the established bioactivity of such heterocyclic frameworks, the synthesized furan-fused pyrimidine derivatives hold potential for applications in pharmaceutical and agrochemical industries. This work underscores the utility of multicomponent reactions in streamlining the synthesis of complex heterocycles.